Odds of anxiety and depression symptoms in school-aged children from official language minority communities - Dupuis, Jérémie B.; Bourque, Jimmy; El Adlouni, Salah-Eddine (Frontiers in Public Health, 2021)
Objectives: The aim of this paper is to assess the odds of suffering from anxiety or depression symptoms based on the presence of certain determinants of health for youth living in the province of New Brunswick, Canada, and in two linguistically different Official Language Minority Communities (OLMCs) in the same province. Methods: With a sample of 22,329 students from grades 7 to 12 in the province of New Brunswick, Canada, logistic regressions were performed to assess each determinant of health's effect on symptoms of anxiety and depression. Results: Some social determinants, like family support, social support and food insecurity, were identified as important determinants of mental health status regardless of linguistic group membership or community membership, while other determinants, such as alcohol use, cannabis use and natural environment, were more prominent in one OLMC than the other. Discussion: Social psychology and public health theories are used in an attempt to explain the results. Limitations and recommendations are also brought forward.

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport